Milder phenotypes of glucose transporter type 1 deficiency syndrome. - Anand, G; Padeniya, A; Hanrahan, D; Scheffer, H; Zaiwalla, Z; Cox, D; Mann, N; Hewertson, J; Price, S; Nemeth, A; Arsov, T; Scheffer, I; et al. (2011)
Glucose transporter type 1 deficiency syndrome (GLUT1DS) is a treatable condition resulting from impaired glucose transport into the brain. The classical presentation is with infantile-onset epilepsy and severe developmental delay. Non-classical phenotypes with movement disorders and early-onset absence epilepsy are increasingly recognized and the clinical spectrum is expanding. The hallmark is hypoglycorrhachia (cerebrospinal fluid [CSF] glucose<2.2 mmol/l) in the presence of normoglycaemia with a CSF/blood glucose ratio of less than 0.4. GLUT1DS is due to a mutation in the solute carrier family 2, member 1 gene (SLC2A1). We present five individuals (four males, one female), all of whom had a mild phenotype, highlighting the importance of considering this diagnosis in unexplained neurological disorders associated with mild learning difficulties, subtle motor delay, early-onset absence epilepsy, fluctuating gait disorders, and/or dystonia. The mean age at diagnosis was 8 years 8 months. This paper also shows phenotypical parallels between GLUT1DS and paroxysmal exertion-induced dyskinesia.